Investigation of the lubrication system in a vehicle axle: Numerical model and experimental validation. (April 2019) - Peng, Qianlei; Zhou, Chi; Gui, Liangjin; Fan, Zijie
Transmission efficiency is the main concern in the design of the lubrication system for a gear transmission system, such as a vehicle axle. This paper presents an optimization method to reduce the churning loss and improve the transmission efficiency in an axle based on the computational fluid dynamics and the response surface method. In this study, the computational fluid dynamics method was applied to simulate the lubrication flow in the axle housing. A numerical model was built for the splash lubrication system that included the entire structure of the hypoid gears, bearings, oil passage, and other parts. The numerical results provided direct visualization of the oil flow inside the axle housing, and the numerical predictions for the oil distribution and churning loss were determined from the numerical result. Furthermore, the influences of the speed, oil level, and oil temperature on the churning loss were investigated. The oil distribution results from the numerical calculations were consistent with the experimental observations, and the error in the predictions for the churning loss was less than 9.3%. The results of this study provide a foundation for subsequent optimization work on the lubrication system of a vehicle axle.